George W.E. Nickelsburg and James C. VanderKam, 1 Enoch 2: A Commentary on the Book of 1 Enoch. Chapters 37-82 (Hermeneia; Minneapolis: Fortress Press, 2012). Pp. xxx, 617. 82. ISBN 978-0-8006-9666-1 - Drawnel, Henryk (The Biblical Annals, 2015)
Book review: George W.E. Nickelsburg and James C. VanderKam, 1 Enoch 2: A Commentary on the Book of 1 Enoch. Chapters 37-82 (Hermeneia; Minneapolis: Fortress Press, 2012). Pp. xxx, 617. 82. ISBN 978-0-8006-9666-1.